Implikatur dalam dialog cerpen “Percakapan Kala Hujan” karya Bernard Batubara - Sari, Dewi Masitoh Arum; Al Fatiya, Rufayda (Maliki Interdisciplinary Journal, 2024)
This research aims to describe the implicatures in the short story entitled "Conversations in the Rain" contained in the short story collection book "Metafora Padma" by Bernard Batubara. The type of research used is qualitative research with text analysis methods. The data used in this research is the text of a conversation in a short story entitled "Conversation in the Rain". Data collection used in this research includes using documentation techniques by reading and recording data from the short story. The technique used in this research uses techniques that include data selection, presentation, and re-checking the data that has been analyzed and its findings. The results of this research are in the form of an explanation of the implicatures in the short story entitled "Conversation in the Rain" which aims to state something, question, influence, convey the opposite meaning, divert and criticize the relationship between a married woman and a single poet.